Предмет: Алгебра,
автор: ВладикРуб
(2х-7)^2*(х-7)=(2х-7)*(х-7)^2
Ответы
Автор ответа:
1
делим правую и левую части уравнения на ( 2X - 7)*( X - 7 )
-----------------------------
2X - 7 ≠ 0 ----> X ≠ 3,5
X - 7 ≠ 0 -----> X ≠ 7
---------------------------------
2X - 7 = X - 7
2X - X = - 7 + 7
X = 0
-----------------------------------
ОТВЕТ Х = 0
-----------------------------
2X - 7 ≠ 0 ----> X ≠ 3,5
X - 7 ≠ 0 -----> X ≠ 7
---------------------------------
2X - 7 = X - 7
2X - X = - 7 + 7
X = 0
-----------------------------------
ОТВЕТ Х = 0
Автор ответа:
2
(2*x-7)²*(x-7) = (2*x-7)*(x-7)²
(х-7)*(2x-7)²-(x-7)²*(2x-7)=(x-7)x*(2x-7)
x-7=0
x=7
x=0
2x-7=0
2x=7
x=7/2
x=3 1/2
Ответ:3 1/2,7,0
(х-7)*(2x-7)²-(x-7)²*(2x-7)=(x-7)x*(2x-7)
x-7=0
x=7
x=0
2x-7=0
2x=7
x=7/2
x=3 1/2
Ответ:3 1/2,7,0
Похожие вопросы
Предмет: Окружающий мир,
автор: margoshafedoro
Предмет: Английский язык,
автор: Sophi07
Предмет: Русский язык,
автор: мария0072004
Предмет: Русский язык,
автор: sonikblekyt
Предмет: Русский язык,
автор: 01312008zneya